FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN LINDUNG NILAI PADA PERUSAHAAN MANUFAKTUR DI BEI - Dwi Dosi Kurniawati; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTTrade does not only cover domestic but also foreign trade also occurs inthe current company commonly referred to as international trade. With theexistence of inter-country trade it will happen fluctuations in currency exchangerates that cause risks or losses. To overcome the uncertain losses, Hedgingdecisions with dervative instruments can be used to protect the assets to avoidlosses. Hedging (hedging) is one of the strategies used to reduce the incidence ofunforeseen risks.This study aims to determine whether MTBV (Market to Book Value) andLiquidity can influence Hedging decision making on manufacturing companies inBEI. And obtained a sample of 6 manufacturing companies listed in BEI duringthe period 2010-2016. With sample selection criteria using purposive sampling,and the technique used is multiple linier regression analysis. The results obtainedthat MTBV (Market to Book Value) and Liquidity have no significant effect onHedging decision making.Key Word : MTBV (Market to Book Value), Liqidity, Hedging.